Exposure of Larvae to Sublethal Thiacloprid Delays Bee Development and Affects Transcriptional Responses of Newly Emerged Honey Bees - Li, Bin; Ke, Li; Li, Ai-Rui; Diao, Qing-Yun; Wang, Qiang; Liu, Yong-Jun (Frontiers in Insect Science, 2022)
Understanding the cause of honey bee (Apis mellifera) population decline has attracted immense attention worldwide in recent years. Exposure to neonicotinoid pesticides is considered one of the most probable factors due to the physiological and behavioral damage they cause to honey bees. However, the influence of thiacloprid, a relatively less toxic cyanogen-substituted form of neonicotinoid, on honey bee (Apis mellifera L.) development is not well studied. The toxicity of sublethal thiacloprid to larvae, pupae, and emerging honey bees was assessed under laboratory conditions. We found that thiacloprid reduced the survival rate of larvae and pupae, and delayed the development of bees which led to lower bodyweight and size. Furthermore, we identified differentially expressed genes involved in metabolism and immunity though RNA-sequencing of newly-emerged adult bees. GO enrichment analysis identified genes involved in metabolism, catalytic activity, and transporter activity. KEGG pathway analysis indicated that thiacloprid induced up-regulation of genes related to glutathione metabolism and Toll-like receptor signaling pathway. Overall, our results suggest that chronic sublethal thiacloprid can affect honey bee colonies by reducing survival and delaying bee development.